Mangrove Community Structure in the Teluk Buo, Bungus Teluk Kabung Sub-District, Padang Regency, Sumatera Barat - Ofrizal '; Adriman '; M Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Mangrove forest in the Teluk Buo Village has been degraded due to anthropogenic activities. To understand the mangrove community structure in that area, a research was carried out in February-Juny 2017. A purposive sampling method was applied and there were 3 stations with 3 transec lines in each station. Along the line, 3 quadrans (10 x 10 m) were used for tree sampling; 3 quadrans (5 x 5 m) for sapling sampling and 3 quadrans (2 x 2 m) for seedling sampling. Mangroves were then identified. Relative density and diversity index of the mangrove were calculated. Results shown that there were 7 mangrove species, namely Rhizopora apiculata, Bruguiera gymnorrhiza, Ceriops tagal, Sonneratia ovata, Scyphiphora hydrophyllacea, Aegiceras corniculatum, and Lumnitzera littorea. The most common species was R.apiculata. The value of relative density of the mangrove was 333-944 p/ha (scarce and damage), and that of the diversity index is medium (1.10-1.55).Keywords: Mangrove, Rhizopora apiculata, Diversity